Depicting Visual Motion in Still Images: Forward Leaning and a Left to Right Bias for Lateral Movement. (February 2015) - Walker, Peter
What artistic conventions are used to convey the motion of animate and inanimate items in still images, such as drawings and photographs? One graphic convention involves depicting items leaning forward into their movement, with greater leaning conveying greater speed. Though this convention could derive from the natural leaning forward of people and animals as they run, it is also applied to depictions of inanimate objects (eg cars and trains). It is proposed that it is this convention that allows the italicization of text to convey notions of motion and speed. Evidence for this is obtained from three sources: the use of italicization on book covers (in book titles); judgments of typeface connotations; and performance measures during the semantic classification of words appearing in italicized and non-italicized fonts. Inspection of the availability of italic fonts in Hebrew indicates an additional artistic convention for conveying motion, based on a fundamental bias, yet to be confirmed, for people to expect to see, or prefer to see, lateral movement (real or implied) in a left to right direction, rather than a right to left direction. Evidence for such a bias is found in photographs of a range of animate and inanimate items archived on Google Images. Whereas a rightward bias is found for photographs of animate and inanimate items in motion (the more so, the faster the motion being conveyed), either no bias or a leftward bias is found for the same items in static pose. Possible origins of a fundamental left to right bias for visual motion, and future lines of research able to evaluate them, are identified.